Pemberdayaan Bank Sampah Masyarakat untuk Mewariskan Budaya Lokal Berlatar Etnomatematika Geometri pada Siswa Sekolah Dasar Desa Tegalsari - Ambarwati, Reza; Safrida, Lela Nur; Suwito, Abi (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
One of the cultural behaviors of local wisdom that is starting to disappear is related to how manage the "garbage". Several communities still throw garbage out of place, such as in the river. On the other hand, the effects of this waste that was disposed of carelessly are very long-term for human health and also the environment. This culture is eventually emulated by their children and grandchildren who are still in school. For this reason, community awareness regarding waste needs to be directed, one of which is the management of a community waste bank. In Tegalsari Village, Ambulu Jember there is one Cipta Mandiri Waste Bank that has been operating for the last 3 years. The Waste Bank activity went quite well, but less than 20% of the community participated, especially young people and children who were less interested. So that the empowerment of the Waste Bank needs to be supported in order to be able to pass down the local culture of being aware of waste, especially for elementary school students through the socialization and education of ethnomathematics worksheets in the elementary school. The results of the activity showed that 78% of students wanted to take part in the waste bank around their homes and they enjoy learning with ethnomathematics worksheets about garbage.